Preference and Values of Stroke Interventions, Kingdom of Saudi Arabia - Reem Alamri; Adel Alhazzani; Saeed A. Alqahtani; Hayfa Al-Alfard; Shahad Mukhtar; Khadejah Alshahrany; Faisal Asiri (Neurology Research International)
Background. Acute ischemic stroke (AIS) occurs when there is a sudden occlusion of the arterial blood supply to part of the brain resulting in sudden focal neurological deficits. Recent major clinical trials of reperfusion therapy had proved the efficacy of timely stroke intervention to restore blood flow. Development of acute stroke protocols waiving the informed consent to obtain necessarily brain images or provide thrombolytic therapy is important to streamline and organize efforts to achieve the goal of early intervention and better functional outcome. Objective. This study aims to identify the preference and values of acute stroke interventions standard of care therapy without informed consent in the absence of surrogate decision-makers. Methods. A cross-sectional survey was conducted in the Kingdom of Saudi Arabia using an electronic questionnaire. The questionnaire addressed the patients' preference of acute stroke protocol waiving the informed consent for hyperacute brain images and delivering thrombolytic therapy or mechanical thrombectomy in absence of surrogate. All Saudi population aging from 18 to 65 years were invited to participate. Results. The study included 2004 participants with ages ranging from 18 to 65 years with mean age of 30.1 years. About 66% of the participants were females and 95% were Saudi. Overall, 90.5% of the participants agreed on performing computed tomography angiography (CTA) by the medical staff for the acute strokes without consenting followed by 79% for thrombolytic therapy, 70.8% for mechanical thrombectomy, and only 49.3% for acute lifesaving surgical intervention. Conclusion. Researchers found that the high percentage of participants had favorable response and positive perception toward providing acute stroke intervention and mechanical thrombectomy without informed consent. However, the study showed skeptical acceptance among participants regarding invasive surgical measures.